Mycoplasma bovis is associated with Mannheimia haemolytica during acute bovine respiratory disease in feedlot cattle - Valeris-Chacin, Robert; Powledge, Sherri; McAtee, Taylor; Morley, Paul S.; Richeson, John (Frontiers in Microbiology, 2022)
Bovine Respiratory Disease (BRD) represents a significant burden to the health of feedlot cattle and the profitability of the beef industry in the US. Mannheimia haemolytica is widely regarded as the primary bacterial pathogen driving acute BRD. While Mycoplasma bovis is most commonly implicated in chronic cases of BRD, this agent’s potential role in acute stages of BRD is unclear. Therefore, this study aimed to evaluate potential associations between M. bovis and M. haemolytica during acute BRD in feedlot cattle. Nasal swabs (n=1044) were collected over time from feedlot cattle (n=270) enrolled in an experiment assessing the effect of vaccination for Bovine Respiratory Syncytial Virus (BRSV). Swabs were analyzed for detection of M. bovis, M. haemolytica, Pasteurella multocida, Histophilus somni, and BRSV via multiplex qPCR assays. Data were analyzed using inverse conditional probability weighted (ICPW) logistic regression models to investigate potential effects of M. bovis presence on arrival (d0), day seven (d7) and day14 (d14) post-arrival on M. haemolytica prevalence on day 28 (d28) post-arrival, adjusting for the previous history of P. multocida, H. somni, BRSV, BRD morbidity, and body weight. The potential association between time-to-BRD detection and M. bovis presence on d0, d7, and d14 post-arrival, was inferred via an ICPW time-to-event model. The presence of M. bovis in nasal swabs collected on d7 post-arrival was significantly associated with an increase in the prevalence of M. haemolytica on d28 (prevalence difference: 45%; 95% Confidence Interval: 31%, 60%; P-value<0.001). Significant time-varying coefficients for M. bovis presence were detected at d0, d7, and d14 post-arrival in the ICPW time-to-event model (P-value<0.001). The shortest median time-to-BRD detection was 29 days in cattle that were M. bovis positive on d0, d7, and d14 post-arrival and in those that were positive on d0 and d14 post-arrival. Under the conditions of this study, our findings suggest that M. bovis may be influencing the respiratory environment during the acute phase of BRD, increasing the abundance of M. haemolytica, which could have important impacts on the occurrence of BRD.